Analysis of Adiponectin, TNF-α, and Biochemical Markers in Fallujah Atherosclerosis Patients - Amenh Muhammed Abdulrahman (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Background: Atherosclerosis is a chronic inflammatory cardiovascular disorder strongly associated with elevated low-density lipoprotein cholesterol (LDL-C) levels and serves as a major predictor of adverse cardiovascular events. This study aimed to investigate the relationship between inflammatory markers (adiponectin and TNF-α) and key biochemical parameters in atherosclerosis patients. Methods: A case-control study was conducted on 60 participants (aged 40–65 years) recruited from private cardiac clinics in Fallujah, Iraq, between October and December 2024. Subjects were stratified into two groups: 30 atherosclerosis patients (diagnosed by specialists) and 30 age-matched healthy controls. Blood samples were collected, centrifuged, and analyzed for CRP, TNF-α, adiponectin, PAI-1, MDA, GSH, sodium (Na), and magnesium (Mg) levels using standardized biochemical assays. Statistical analysis was performed using SPSS, with significance set at *p* ≤ 0.001. Results: Atherosclerosis patients exhibited significantly elevated serum levels of CRP (2.21 ± 14.46 vs. 1.07 ± 7.76 mg/dL), TNF-α (15.14 ± 120.86 vs. 4.27 ± 65.16 pg/mL), PAI-1 (6.52 ± 0.82 vs. 2.02 ± 0.42 ng/dL), MDA (590.26 ± 29.64 vs. 155.52 ± 25.19 ng/mL), and Na (140.16 ± 1.18 vs. 125.46 ± 6.17 nmol/L) compared to controls (*p* ≤ 0.001). Conversely, adiponectin (0.18 ± 1.81 vs. 0.67 ± 4.18 mg/dL), GSH (22.79 ± 1.37 vs. 40.81 ± 3.05 μg/mL), and Mg (1.46 ± 0.175 vs. 1.84 ± 0.67 nmol/L) were markedly reduced in patients. ROC curve analysis demonstrated perfect diagnostic accuracy (AUC = 1.0) for CRP, TNF-α, and adiponectin in distinguishing patients from controls. Conclusion: The study highlights pronounced dysregulation of inflammatory, oxidative, and metabolic pathways in atherosclerosis, with CRP, TNF-α, and adiponectin serving as robust discriminative biomarkers. These findings underscore the potential of targeting these pathways for therapeutic intervention and early diagnosis.